EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON STOCK PRICES ON REGISTERED METAL AND SIMILAR COMPANIES ON THE INDONESIA STOCK EXCHANGE - Rambe, Ihsan; Nurwahyuni, Nurwahyuni; Saripuddin Hasibuan, Jasman (CV. Radja Publika, 2021)
The stock price is the price that occurs in the stock market at a certain time and the stock price is determined by market participants. The high and low price of these shares is determined by the demand and supply of these shares in the capital market. Current Ratio is a ratio to measure the company's ability to pay its long-term debt approach which is due immediately when billed in its entirety. and Debt to Equity Ratio is a ratio that shows the percentage of provision of funds by shareholders to lenders. The higher the ratio, the lower the company's funding provided by shareholders. This study aims to determine whether there is an effect of Current Ratio and Debt to Equity Ratio on stock prices either partially or simultaneously. This study uses financial management theory related to the variables of stock price, current ratio, debt to equity ratio. The approach used is an associative approach. The population in this study are Metal & Similar companies listed on the IDX for the period 2014-2018. Samples were taken using purposive sampling method, in order to obtain 6 companies as samples. The results show that: (1) the effect of the current ratio on stock prices has no effect; (2) the effect of Debt to Equity Ratio on stock prices has an effect; (3) the influence of the Current Ratio and Debt to Equity Ratio on stock prices simultaneously has an effect.